The interrelation between body mass index and post-dural puncture headache in parturient women - Serbülent Gökhan Beyaz; Tolga Ergönenç; Aykut Saritaş; Fatih Şahin; Ali Metin Ülgen; Ali Eman; Burcu Doğan (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Post-dural puncture headache is seen more frequently in pregnant women due to stress, dehydration, intra-abdominal pressure, and insufficient fluid replacement after delivery. Obesity protects against post-dural puncture headache in pregnant women; increased intra-abdominal fat tissue reduced cerebrospinal fluid leakage by increasing the pressure in the epidural space. Therefore, this study investigated the influence of body mass index on post-dural puncture headache in elective cesarean section patients in whom 27G spinal needles were used. Material and Methods: The study included 464 women who underwent elective cesarean section under spinal anesthesia. Dural puncture performed with a 27G Quincke spinal needle at the L3-4 or L4-5 intervertebral space and given 12.5 mg hyperbaric bupivacaine intrathecally. The patients were questioned regarding headache and low back pain 6, 12, 24, and 48 h after the procedure, and by phone calls on days 3 and 7. Results: Post-dural puncture headache developed in 38 (8.2%) patients. Of the patients who developed post-dural puncture headache, 23 (60.5%) had a body mass index <30 and 15 (39.5%) had a body mass index ≥30. Of the patients who did not develop post-dural puncture headache, 258 (60, 6%) had a body mass index <30 and 168 (39, 4%) had a body mass index ≥30. Conclusion: This prospective study found the body mass index values did not affect post-dural puncture headache in the elective cesarean section performed under spinal anesthesia.